Kemampuan Pemecahan Masalah Matematis ditinjau dari Self-Efficacy pada Project-based Learning berbasis APOS berbantuan E-modul - Sa'diyah, Riska Nur; Dwijanto, Dwijanto; Wijayanti, Kristina (Mathematics Education Study Program, 2024)
This research aims to analyze the effectiveness of Project-based learning based on APOS assisted by e-modules on students' mathematical problem-solving abilities, analyze the influence of self-efficacy on students' mathematical problem-solving abilities, and describe mathematical problem-solving abilities, a review of students' self-efficacy in Project-based learning based on APOS assisted by e-modules. The method used was a mixed method. The population came from 10th-grade students of the TKR Department of SMK Negeri 10 Semarang. The sample was selected using a simple random sampling technique. The subjects in this study were 2 students selected for each self-efficacy classification. Data collection techniques used mathematical problem-solving ability tests, self-efficacy questionnaires, and interviews. The quantitative data were analyzed by the t-test, z-test, two-sample mean test, n-gain test, and regression test. The qualitative data were analyzed by data collection, data presentation, data reduction, and conclusion. The research results show (1) Project-based learning based on APOS assisted by e-modules is effective learning on students' mathematical problem-solving abilities, (2) there is an influence between self-efficacy and students' mathematical problem-solving abilities of 68%, and (3) the results obtained from the analysis of mathematical problem-solving in terms of self-efficacy where 4 students with high self-efficacy were able to complete four indicators which had high category mathematical problem-solving abilities, 20 students with low self-efficacy tended to be able to complete three indicators which had medium category mathematical problem-solving abilities, and 5 students with low self-efficacy tend to only be able to complete two indicators of which 2 students have moderate category mathematical problem-solving abilities and 3 students have a low category.